THU0127 The dynamics of mental disorders frequency in complex dmards, biologics and antidepressants treatment of rheumatoid arthritis patients. (15th June 2017) - Abramkin, A; Lisitsyna, T; Veltishchev, D; Seravina, O; Kovalevskaya, O; Nasonov, E
Abstract : Background: mental disorders (MD) (anxiety/depressive (ADD) and cognitive (CD)) occur in rheumatoid arthritis (RA) patients (pts) very often, they are usually stress-related and, probably, have common pathogenesis chains with RA. In this connection the disease-modifying anti-rheumatic drugs (DMARDs) and biologics drugs treatment may be effective in ADD in RA-pts. Objectives: to determine the frequency of MD dynamics during DMARDs, biologics and antidepressants treatment of RA-pts in prospective 5yrs study. Methods: 128 RA-pts were enrolled in this study. All of them met the full ACR criteria. 86% RA-pts were women with a mean age of 47, 4±1, 0 (M±m) yrs. RA activity was assessed by DAS28 and was high (5, 25±0, 17 (M±m)) in the beginning of the study. 67% RA-pts were taking prednisone (5±2, 7 mg/day), 80% RA-pts - DMARDs, 26% - biologics (rituximab – 11%, anti-TNF-α – 10%, anti-IL6 – 5%). MD were diagnosed by psychiatrist in accordance with the ICD-10 in semi-structured interview. The severity of depression and anxiety was evaluated by Montgomery–Asberg Depression Rating Scale (MADRS) and Hamilton Anxiety Rating Scale (HAM-A). CD were diagnosed with psychology and neuropsychology methods. ADD were diagnosed in 121 (94, 5%) and CD – in 87 (67, 9%) of RA-pts. Major depressive disorder (MDD) was found in 41 (32%), minor depressive disorder (MinDD) – in 50 (39%) and anxiety disorders (AD) – in 30 (23, 4%) of RA-pts. The occurrences of MD were evaluated in one and five yrs in 105 from 121 (87%) RA-pts divided into the following treatment groups: 1 – DMARDS (n=32), 2 - DMARDs + antidepressants (sertraline or mianserine) (n=37), 3 – DMARDs + biologics (n=27), 4 - DMARDs + biologics + antidepressants (sertraline or mianserine) (n=9). Results: Group 1: the frequency of MDD was increased from 24, 6% to 34, 8% in a year and to 42, 8% in 5 yrs (p=0, 09); MinDD – from 47, 8% to 60, 8% (p=0, 19) and 50% in 5 yrs; the number of pts with AD decreased from 27, 5% to 4, 3% (p=0, 014) and 4, 8% (p=0, 021) accordingly. The frequency of CD was increased from 64, 3% to 78, 3% (p=0, 16) in 5 yrs. Group 2: the frequency of MDD was decreased from 47, 4% to 15, 7% (p=0, 049) in a year and to disappearance of depressive symptoms (p<0, 001) in 5 yrs; MinDD – from 26, 3% to 15, 8% and to disappearance (p<0, 001) in 5 yrs; AD – from 26, 3% to 10, 5% and to disappearance (p<0, 001) in 5 yrs. The frequency of CD was decreased from 78, 9% to 60% (p=0, 25). Group 3: the frequency of MDD was unchanged (40, 7%, 45, 4% and 42, 8% accordingly); the frequency of MinDD was increased not significantly – 40, 7%, 40, 9% and 52, 4%; but AD – was significantly decreased (from 18, 5% - to disappearance in a year (p=0, 042) and 5 yrs (p=0, 047)). The frequency of CD was increased from 77, 8% to 85%. Group 4: the frequency of MDD was decreased significantly from 66, 7% to 16, 7% in a year and to disappearance in 5 yrs (p=0, 03); MinDD and AD were decreased from 16, 7% both to disappearance. The occurrence of CD was decreased from 71, 4% to 57, 1%. Conclusions: the results demonstrated the best positive dynamics of MD (ADD and CD) frequency in the groups of RA-pts receiving antidepressants treatment in combination with DMARDs and biologics. There was no positive dynamics of MD in patients group receiving DMARDs and mild positive dynamics of AD in the group receiving biologics. Disclosure of Interest: None declared